The Habitation and Damage of Mite in Apple and Plum Tree Orchards of Armavir Region - Asatryan, Samvel (ՀԱԱՀ հիմնադրամ)
In 2021-2022, a study of herbivorous (phytophagous) mite habitation and harmfulness was conducted in apple and plum orchards in the Armavir region (RA). Research findings of two-year scientific experiments confirmed that between the two apple varieties the Star Crimson variety had the highest habitation rate of Hawthorn Red Spider Mite (Tetranychus viennensis Zacher), specifically 52.7 % in the first year, and 55.5 % in the second year. Among the three plum varieties, Vengerka Italian had the highest habitation rate (49.5 and 53.2 %, respectively) of common spider mites (Tetranychus urticae Koch). Research findings also confirm that at the peak of leaf damage, compared to the Golden Delicious apple variety, the damage caused by Hawthorn Red Spider Mite to the leaves of the Star Crimson apple variety was high in 2021-2022 (43.5 % and 45.0 % respectively). There was relatively high damage caused by Hawthorn Red Spider Mite to the “Vengerka Italian” variety in 2021 and 2022 (39.9 % and 41.0 %, respectively). Effective control measures against phytophagous mites with high habitation in apple and plum orchards will be developed and offered to farmers.
Keywords: Agronomy and Agroecology